Revealing the hidden biodiversity of the Andes: Eleven new species of Axinaea (Melastomataceae, Merianieae) - Fernandez-Hilario, Robin; Murillo-Serna, Jhon S.; Miranda-Montealegre, Gustavo; Ocaña, Daniel M. Tarazona; Fernández-Fernández, Diana; Gámez, Luis; Jaramillo, Nelson; Ulloa, Carmen Ulloa; Goldenberg, Renato; Michelangeli, Fabián A. (Phytotaxa, 2026)
Eleven new species of Axinaea (Melastomataceae, Merianieae) are described and illustrated from the Andes. The new species are A. auriculata and A. johnjuliusii from Venezuela, A. frustrata, A. paisa and A. titanica from Colombia, A. andina, A. kiru, A. matangae and A. olivacea from Ecuador, A. huancabambae from Ecuador and Peru, and A. yunga from Bolivia. We provide morphological descriptions along with comments on related species and geographic distribution. Also, we discuss the current diversity and taxonomy of Axinaea in the Andes. With these discoveries, Venezuela, Colombia, Ecuador, Peru, and Bolivia now have a total of seven, 12, 21, 18, and two species of Axinaea, respectively. Finally, we present a preliminary list of the 50 currently accepted Axinaea species.